Synthesis and properties of 1-(2-(alkylamino)-2-oxoethyl) pyridinium chloride surfactants. (1st April 2013) - Wang, Li-yan; Qin, Hong-lei; Wang, Lei; Huo, Shi-chao; Zhao, Bing; Song, Bo; Yan, Tie
A series of 1-(2-(alkylamino)-2-oxoethyl) pyridinium chloride surfactants was designed and synthesised by two steps. Four new compounds were obtained. The structures of all the synthesised compounds have been characterised by IR, 1H NMR and elemental analyses. Surface activity and antibacterial activity of 1-(2-(alkylamino)-2-oxoethyl) pyridinium chloride surfactants were investigated. The critical micelle concentration and C20 values of the synthesised surfactants are low. The synthesised surfactants have good antibacterial activity for sulfate-reducing bacteria, metatrophic bacteria and iron bacteria in oil field injection water.